Evaluation of carrying capacity based on land capability of Kulon Progo Regency as an input for spatial planning in the new aerotropolis era - Litasari, Ulfah Choerunnisa Nurul; Widiatmaka; Munibah, Khursatul; Machfud (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2022)
The new aerotropolis era due to airport construction in Kulon Progo has stimulated regional development and changed the image of the area from rural to urban-oriented. The negative impact of rapid growth, such as the urban sprawl, can be mitigated through sustainable spatial planning. Therefore, this study aims to evaluate the carrying capacity based on the land capability of both existing and official land use planning. The matching criteria method was used to conduct the capability evaluation. According to the analysis results, 56.13% of the Kulon Progo area was dominated by moderate to low land capability classes (V-VIII) with the main inhibiting factor as slopes. Furthermore, the evaluation of conformity with land use/land cover (LULC) in 2020 showed most land uses were in not conform (NC) and conditionally conform (CC) status. The area of land use that did not conform with its carrying capacity was 8,286.44 ha which was distributed in the southern part. Meanwhile, an evaluation of the official land use planning of the area showed 57% of the plan was conform (C) with land capability. Therefore, the carrying capacity of the land in Kulon Progo is in reasonably good condition. However, planning interventions should be carried out for areas with not conform status.